GLOBAL CLIMATE CHANGE AND NATURAL DISASTERS: A THREAT TO SUSTAINABLE FOOD PRODUCTION AND FOOD SECURITY OF PAKISTAN - Shahbaz Farooq, Muhammad; Fatima, Hira (REVISTA DE AGRICULTURA, 2022)
Since the last few decades, climate change had hardly hit the poor economy-holding countries, Pakistan is among these which is very prone to climate disasters due to its geography. This study is analyzing the climate change in Pakistan by reviewing the negative impacts in terms of disasters on the economy and livelihoods. Geographical location, socioeconomic factors and continuous episodic climatic fluctuations around the globe have made Pakistan much vulnerable climate disasters like droughts, floods, extreme events, etc. Therefore, this study is concluding by highlighting the susceptibility to food security and the economy of Pakistan considering the negative impacts of disasters undergoing due to climate change. It moved towards the past to have an overview where and when Pakistan was hardly hit by severe hazards and what losses it brought to economy and livelihoods in the last few decades. Further, this paper is expressing the local scale vulnerability to diverse disasters by analyzing natural or human-intervened factors. Furthermore, it expresses about the incidence of poorest towards climate disasters considering the geographic, climatic and socioeconomic factors of each region. Finally, it suggests that the countries like Pakistan are in dire need to quickly address the negative impacts of climate changes regionally and locally to overcome the losses by giving mitigation and adaptation approaches instead of wasting resources towards recovering.